Respostas

2014-07-29T22:04:11-03:00
6x^2-x-1 = 0 \\  \\  \\ A= 6  \\  \\ B=-1 \\  \\ C= -1



Δ = b² - 4*a*c
Δ= (-1)²- 4*6*(-1)
Δ= 1+24
Δ= 25


x=  \frac{-1 \frac{+}{} }{2*6}  \sqrt{25}  \\  \\ x=  \frac{-1 \frac{+}{}5 }{12} \\  \\ x'=   \frac{-1-5}{12} \\ \\  x'= \frac{-6:6}{12:6}  =\boxed{ \boxed{ \frac{-1}{2}}} \\  \\  \\ x"=  \frac{-1+5}{12}  \\  \\ x=  \frac{4:4}{12:4}  \\ x"=====\boxed{ \boxed{ \frac{1}{3}}}

(x'+1) . ( x"+1) \\  \\ ( \frac{-1}{2} +1) . ( \frac{1}{3}+1) \\  \\  \frac{-1}{2}  . \frac{1}{3} =\boxed{  \frac{-1}{6}} \\  \\  \frac{-1}{6}+ \frac{-1}{2}  + \frac{1}{3}+1 \\  \\  \frac{1+1}{6}  = \frac{2:2}{6:2} =  \boxed{\boxed{\boxed{\frac{1}{3}}}}